PENERAPAN MODEL PEMBELAJARAN BERBASIS GAMES (TIC TAC TOE) DALAM UPAYA MENINGKATKAN PEMAHAMAN KONSEP PADA MATA DIKTAT ELEKTRONIKA DASAR - Enjang A. Juanda; Tjetje Gunawan; Dede Mujiburrohman (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTPre-experimental reserach had been conducted on the result of understanding concept for Basic Electronics course after the implementation of tic tac toe game on linear passive component. The sample of the study was the tenth grade students of MA Raudlatutta’allum Cidahu, Tamanjaya, Tamansari, Tasikmalaya. The purpose of the reserah is to reveal the improvement of understanding concept for Basic Electronics course on linear passive component after the implementation of tic tac toe game. The result of the study  showed that the implmentation of this game could improve the students’understanding concept toward the material with significant and high gain.    Keywords : understanding concept, basic electronics, tic tac toe game